First metatarsal single-screw minimally invasive chevron-akin osteotomy: A cost effective and clinically reliable technique - Li, Xueqian; Zhang, Jieyuan; Fu, Shaoling; Wang, Cheng; Yang, Fan; Shi, Zhongmin (Frontiers in Surgery, 2023)
Purpose The common disease hallux valgus results in foot discomfort and dysfunction. Less soft tissue damage and faster wound healing have made minimally invasive surgery (MIS) more popular. However, little research has compared the fixation results of minimally invasive chevron-akin (MICA) osteotomy thus far. In this study, the clinical and radiographic results of MICA with first metatarsal single- or dual-screw fixation are being examined. Methods A total of 107 feet of 103 patients with mild to moderate symptomatic hallux valgus treated MICA from January 2018 to June 2020 were retrospective evaluated, with at least 12-months follow-up. 51 patients underwent single-screw fixation procedures and 52 patients received dual-screw fixation procedures. Patients were assessed preoperatively and at the final follow-up with radiographic measurements [hallux valgus angle (HVA), intermetatarsal angle (IMA) and distal metatarsal articular angle (DMAA)] and clinical scores (american orthopaedic foot and ankle society (AOFAS) forefoot score, visual analog scale (VAS) and Manchester-Oxford Foot Questionnaire (MOxFQ) scores). The coughlin satisfaction scores were also obtained. Results Both groups showed significantly improved HVA, IMA and DMAA at the final follow-up (P < 0.001). Regarding clinical outcomes, the AOFAS, VAS and MOxFQ in two categories also significantly improved postoperatively (P < 0.001). There was no obvious difference in the clinical and radiographic outcomes between the two groups (HVA, P = 0.833; IMA, P = 0.073; DMAA, P = 0.35; AOFAS, P = 0.48; VAS, P = 0.86; MOxFQ, P = 0.87). However, the single-screw fixation group showed significantly lower operation time and less number of intraoperative fluoroscopy (P < 0.001). No serious complications were observed in either group. The single-screw fixation technique saves at least 1,086 compared with the dual-screw group. Conclusion At the final follow-up, both the single- and dual-screw fixation groups had comparable good to excellent clinical and radiographic outcomes, as well as a similar incidence of complications. Additionally, the single-screw fixation group reduces overall surgical costs, number of intraoperative fluoroscopy and operational time.